2015
DOI: 10.1007/s15010-015-0791-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in immune responses to infectious diseases

Abstract: Understanding sex-based differences in immunity during different infectious diseases is crucial in order to provide optimal disease management for both sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
130
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 47 publications
9
130
0
6
Order By: Relevance
“…The onset of puberty is associated with the numbers and functions of circulating granulocytes and monocytes, which are decreased but activated in females due to rising levels of progesterone in the setting of ovulation or pregnancy (7, 8). In addition, myeloid cells and lymphocytes express receptors for estrogen, progesterone and androgens, which orchestrate transcriptional pathways, ligand dependent or ligand independent signaling cascades that influence innate and adaptive immune responses to viruses (912). With regard to gene dosage on sex chromosomes, X-linked genes such as IL-13, IL-4, IL-10, Xist, Tlr7, FoxP3 on X chromosome and Sry (testis-determining factor), Sox9 (SRY-box 9) on Y chromosome may underlie sexually dimorphic responses that contribute to stronger innate, cellular and humoral immune responses and susceptibility to autoimmune diseases in females compared with males (1315).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of puberty is associated with the numbers and functions of circulating granulocytes and monocytes, which are decreased but activated in females due to rising levels of progesterone in the setting of ovulation or pregnancy (7, 8). In addition, myeloid cells and lymphocytes express receptors for estrogen, progesterone and androgens, which orchestrate transcriptional pathways, ligand dependent or ligand independent signaling cascades that influence innate and adaptive immune responses to viruses (912). With regard to gene dosage on sex chromosomes, X-linked genes such as IL-13, IL-4, IL-10, Xist, Tlr7, FoxP3 on X chromosome and Sry (testis-determining factor), Sox9 (SRY-box 9) on Y chromosome may underlie sexually dimorphic responses that contribute to stronger innate, cellular and humoral immune responses and susceptibility to autoimmune diseases in females compared with males (1315).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that girls produce stronger immune responses to several viruses [12,13]. Thus, our observation may reflect a difference in immune responsiveness to influenza A virus rather than in the number of infections per se.…”
Section: Discussionmentioning
confidence: 56%
“…It is widely recognised that females exhibit more robust innate and adaptive immune responses to self and foreign antigens than males, which is thought to be due to hormonal, genetic and environmental influences . Inflammation appears to be a common underlying feature of many disorders that disproportionally affect women and glucocorticoids are a cornerstone in the treatment of many inflammatory disorders .…”
Section: Discussionmentioning
confidence: 99%